Equalisation as goal of centre-state transfers: Iqbal Gulati's golden legacy - Bagchi, Amaresh (2002)
The finest legacy of the late I S Gulati is in the field of federal financial relations. The goal set by Gulati for federal transfers, viz, equalisation of primary civic sservics based on acceptable standards or norms is unexceptionable. Norm-based equalisation serves both equity and efficiency. It is to be hoped that the legacy left behind by Gulati will be picked up by the Twelfth Finance Commission which is to be formed soon. - Reproduced.
Keywords: Intergovernmental financial relations